Compressive Optic Neuropathy (CON) Secondary to Inflammatory Polyp Mimicking Lymphoma: A Rare Manifestation - Danniswara, Fadia Ghaisani; Agustini, Lukisiari (Universitas Airlangga, 2023)
Introduction: Compressive optic neuropathy (CON) is the impairment of optic nerve function by space-occupying lesions that mechanically compress the optic nerve or optic tract. CON can arise from either intrinsic or extrinsic compression, and determining the underlying cause is important to approach the correct management. The objective of this case report is to present a rare case of CON secondary to an inflammatory polyp that mimicking lymphoma. Case Presentation: A 68-year-old male patient came to the neuro-ophthalmology clinic with a chief complaint of blurry vision in his left eye since three months ago that was getting worse until he lost his vision accompanied by drooping of the upper left eyelid. He also felt pain in his left eye, nausea, vomiting, and headache. Visual acuity of the right eye was 5/5 and the left eye had no light perception. Ocular motility of the left eye was restricted in all gaze. The pupil was 6 mm with no light reflex, and edema in the optic nerve head in the left eye was found from the posterior segment. The patient's MRI showed soft tissue thickening on the left orbital apex – left optic canal – left anterior cavernous sinus and enlargement of left medial rectus muscle with encasement of the left optic nerve, and from post-contrast showed contrast enhancement that suggested a lymphoma. He was diagnosed with CON secondary to lymphoma and was given Methylprednisolone 32 mg three times a day orally. Conclusions: Several differential diagnoses resemble the findings of CON secondary to inflammatory polyp. Some diagnostic examination must be done to exclude the other diagnosis to give a proper treatment for the patient.